Effect of Intermittent Positive Pressure Ventilation on Depth of Anaesthesia during and after Isoflurane Anaesthesia in Sulphur-Crested Cockatoos (Cacatua galerita galerita) - Saul Chemonges (Veterinary Medicine International)
This study aimed to determine the effect of intermittent positive pressure ventilation (IPPV) on the depth of inhalation anaesthesia in parrots. Anaesthesia was induced with 3.0% isoflurane in six Sulphur-crested Cockatoos (Cacatua galerita galerita) and maintained using either 1.5% or 3.0% during spontaneous ventilation (SV) or IPPV at 6 (IPPV-6) or 12 (IPPV-12) breaths per minute. The time taken for the appearance of somatic reflexes and the return of SV after IPPV was recorded. During recovery, the body jerk, beak, eye, and shivering reflexes appeared after 126 ± 27 s, 133 ± 26 s, 165 ± 34 s, and 165 ± 44 s, respectively. All cockatoos developed apnoea after IPPV-12 and only some did after IPPV-6. Return of SV after IPPV-12 was delayed compared to IPPV-6. Recovery times after the SV runs were significantly different between 1.5% and 3.0% isoflurane anaesthesia. Similarly, after IPPV, the recovery times were significantly different between 1.5% and 3.0% isoflurane anaesthesia. Recovery times after 3.0% inhaled isoflurane were longer than those of 1.5% inhaled isoflurane. In conclusion, cockatoos recovering from isoflurane anaesthesia are likely to exhibit body jerk, beak, eye, and shivering reflexes in that order. IPPV increases the depth of anaesthesia in a rate and dose-related manner and prolongs recovery.